الحاجات الارشادية لدى الطلاب لتحقيق التوافق النفسيالاجتماعي دراسة استكشافية على عينة من تلاميذ السنة اولى ثانوي (ادبي علمي) لثانوتين حمدي قدور - الامام الغزالي لمدينة الاغواط - عوالي خويلد; لطرش بشرى; عائشة بدوي (My University, 2022)
The study aimed to identify the counseling needs in achieving psychosocial adjustment among first year secondary students in the state of Laghouat. Of 90 male and female students for the first year of secondary school at Imam Al-Ghazali and Hamdi Kaddour High Schools, from the scientific and literary specializations. Our study reached the following results: 1- The level of psychosocial adjustment among middle school first year students